Le lussazioni dell’arto superiore in età evolutiva - Toniolo, R.M.; Giordano, M.; Aulisa, A.G. (Lo Scalpello - Journal, 2018)
UPPER LIMB DISLOCATIONS IN THE DEVELOPING SKELETON Children have a high propensity to injure their upper limbs. Younger children use their hands to discover and get to know the world around them, while older ones and the teenagers are increasingly dealing with recreational physical activities and agonistic sports events. Upper extremity lesions may occur from the shoulder to the fingers. As regards the biomechanical features in the developing skeleton, bones and physes are usually involved while, on the other hand, dislocations and subluxations of the upper extremities are uncommon in children, because of the relative weakness of the epiphyseal plates. Correct diagnostic procedures and consequent therapeutic treatments are fundamental to achieve the best possible outcome.